(untitled) (Global Journal of Management and Business Research, 2018)
The losses and bankruptcy that has led to many business organizations and also that are leaving many victims with the handling of fraud and crimes that strengthen corruption and that leads to companies around the world and especially in Latin America, makes that the executives and the employees of any level of the same ones contribute to that this scourge be strengthened in the routine work and in the development of the daily tasks, for that reason the importance of the forensic audit, that does, that investigations are carried out that help to detect those situations already committed, identifying who are the perpetrators and the impact that these have left to the economy of the victims and to the community as it is the case of the environment, the social, the cultural, the political, the administrative, the financial, technology, education, health among other areas, helping the administration of justice as experts or expert witnesses.